2020
DOI: 10.2196/14826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Health-Related WeChat Public Accounts: Cross-Sectional Study

Abstract: Background As representatives of health information communication platforms accessed through mobile phones and mobile terminals, health-related WeChat public accounts (HWPAs) have a large consumer base in the Chinese-speaking world. However, there is still a lack of general understanding of the status quo of HWPAs and the quality of the articles they release. Objective The aims of this study were to assess the conformity of HWPAs to the Health on the Ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…One limitation is that we only focused on Chinese-language apps available on the two most popular operating systems (Android and iOS), and thus missed apps available in other languages or on other operating systems. Although WeChat public accounts have been increasingly used as mHealth tools in China [ 46 ], we did not include WeChat public accounts for AS management, such as the Smart-phone SpondyloArthritis Management System [ 11 ]. We searched for apps in two of the most popular app stores (the Huawei and Apple App Stores) for Android and iOS operating systems in China, but apps exclusively in other app stores (eg, Microsoft) were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation is that we only focused on Chinese-language apps available on the two most popular operating systems (Android and iOS), and thus missed apps available in other languages or on other operating systems. Although WeChat public accounts have been increasingly used as mHealth tools in China [ 46 ], we did not include WeChat public accounts for AS management, such as the Smart-phone SpondyloArthritis Management System [ 11 ]. We searched for apps in two of the most popular app stores (the Huawei and Apple App Stores) for Android and iOS operating systems in China, but apps exclusively in other app stores (eg, Microsoft) were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(Luo et al, 2019 ). (ii) The establishment of the information database provided parents with a platform to actively learn about osteosarcoma-related information, which indicated that they might be more prepared to manage their children (Wang et al, 2020 ). (iii) Through the one-to-one or group chat mode of WeChat, parents could get in touch with the nursing staff timely to obtain professional advice; they could also communicate with other members to exchange experiences, encourage each other, and reduce negative emotions (Luo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic of Covid-19 has affected the patterns of urological education to a certain extent, and Published by Francis Academic Press, UK -77-medical students have benefited from e-learning during that time. To avoid misgivings of the unprofessional contents when establishing an online medical learning platform through social media like WeChat, the Health on the Net Foundation Code of Conduct (HONcode) should be applied to evaluate the suitability of articles disseminated by health-related WeChat public accounts [29]. Besides, the peerreview system may be taken into consideration for the appraisal of original online learning resources and a quick double-check system can be used in the technical review of compiled or translated contents.…”
Section: Perspectivementioning
confidence: 99%